Energy-tunable photocatalysis by hot carriers generated by surface plasmon polaritons. Issue 12 (6th March 2019) - Ahn, Wonmi; Vurgaftman, Igor; Pietron, Jeremy J.; Pehrsson, Pehr E.; Simpkins, Blake S.
Abstract : Hot carrier generation by surface plasmon polariton was demonstrated in a metal/semiconductor heterofilm and a bare metal film for energy-tunable photocatalysis. Abstract : Noble metals capable of generating hot carriers by plasmon decay promote efficient charge separation with visible light, which opens a new prospect in the fields of photocatalytic energy conversion and solar fuel generation. Recent studies also indicate that by tuning system parameters such as photon energy and plasmon resonance, hot carriers may be injected into specific anti-bonding orbitals of an adsorbed molecule, making it possible for selective photocatalysis. Although numerous metal nanoparticle systems have been devised to harness plasmon-induced hot carriers, little is known for surface plasmon polariton (SPP)-induced hot carrier generation, especially for energy-tunable photocatalysis. In fact, nanoparticles' morphological variations, resonance inhomogeneity, and limited spectral tunability have challenged efficient control over energy-tunable photocatalysis. In this study, we investigated the energy-tunable photocatalysis using SPP-supporting metal film systems including a metal–semiconductor heterofilm (Ag/TiO2 ) and a bare metal film (Au) by measuring electrochemical responses under a continuously-tuned illumination angle. We found that photon-to-carrier conversion efficiency measured in the heterofilm was strongly dependent on photon energy, showing a good agreement with a Schottky transport model. We also found that hot carriers generated in the bare metal film are energetically positioned near the metal's Fermi level, and therefore, chemical reactions can be controlled by tuning electrode potential or solution pH. These results demonstrate that the SPP system could provide a platform for understanding charge transport mechanisms in plasmon-induced photocatalysis and pave a new path for energy-tunable chemical reactions.